Wistar-Kyoto Female Rats Are More Susceptible to Develop Sugar Binging: A Comparison with Wistar Rats - Papacostas-Quintanilla, Helena; Ortiz-Ortega, Víctor Manuel; López-Rubalcava, Carolina (Frontiers in Nutrition, 2017)
The hedonic component of the feeding behavior involves the mesolimbic reward system and resembles addictions. Nowadays, the excessive consumption of sucrose is considered addictive. The Wistar-Kyoto (WKY) rat strain is prone to develop anxiety and addiction-like behavior; nevertheless, a lack of information regarding their vulnerability to develop sugar binging like behavior (SBLB) and how it affects the reward system persist. Therefore, the first aim of the present study was to compare the different predisposition of two rat strains, Wistar (W) and WKY to develop the SBLB in female and male rats. Also, we studied if the SBLB inducing protocol produces changes in anxiety-like behavior using the plus-maze test (PMT) and, analyzed serotonin (5-HT) and noradrenaline (NA) concentrations in brain areas related to anxiety and ingestive behavior (brain stem, hypothalamus, nucleus accumbens and amygdala). Finally, we evaluated whether fluoxetine, a drug that has been effective in reducing the binge-eating frequency, body weight and severity of binge eating disorder, could also block this behavior. Methods: Briefly, WKY and Wistar female rats were exposed to 30% sucrose solution (2 hours, three days per week for four weeks), and fed up ad libitum. PMT was performed between the last two test periods. Immediately after the last test where sucrose access was available, rats were decapitated and brain areas extracted for HPLC analysis. The results showed that both W and WKY female and male rats developed the SBLB. WKY rats consumed more calories and ingested a bigger amount of sucrose solution than their W counterpart. This behavior was reversed by using fluoxetine, rats exposed to the SBLB inducing protocol presented a rebound effect during the washout period. On female rats, the SBLB inducing protocol induced changes in NA concentrations on WKY, but not on W rats. No changes were found in 5-HT levels. Finally, animals that developed SBLB showed increased anxiety-like behavior in the PMT. In conclusion, WKY female rats can be considered as a rat strain more susceptible to develop SBLB.